Seasonal dynamics of light absorption by chromophoric dissolved organic matter (CDOM) in the NW Mediterranean Sea (BOUSSOLE site) - Organelli, E.; Bricaud, A.; Antoine, David; Matsuoka, A. (Pergamon, 2014)
We analyze a two-year time-series of chromophoric dissolved organic matter (CDOM) light absorption measurements in the upper 400 m of the water column at the BOUSSOLE site in the NW Mediterranean Sea. The seasonal dynamics of the CDOM light absorption coefficients at 440 nm (acdom(440)) is essentially characterized by (i) subsurface maxima forming in spring and progressively reinforcing throughout summer, (ii) impoverishment in the surface layer throughout summer and (iii) vertical homogeneity in winter. Seasonal variations of the spectral dependence of CDOM absorption, as described by the exponential slope value (Scdom), are characterized by highest values in summer and autumn at the surface and low values at the depths of acdom(440) subsurface maxima or just below them. Variations of acdom(440) are likely controlled by microbial digestion of phytoplankton cells, which leads to CDOM production, and by photochemical destruction (photobleaching), which leads to CDOM degradation. Photobleaching is also the main driver of Scdom variations. Consistently with previous observations, acdom(440) for a given chlorophyll a concentration is higher than expected from Case I waters bio-optical models. The total non-water light absorption budget shows that surface waters at the BOUSSOLE site are largely dominated by CDOM during all seasons but the algal bloom in March and April. These results improve the knowledge of CDOM absorption dynamics in the Mediterranean Sea, which is scarcely documented. In addition, they open the way to improved algorithms for the retrieval of CDOM absorption from field or satellite radiometric measurements.